1994
DOI: 10.1104/pp.105.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Starch Phosphorylation in Potato Tubers Proceeds Concurrently with de Novo Biosynthesis of Starch

Abstract: l h e in vivo phosphorylation of starch was studied in Solanum tuberosum cv Dianella and Posmo. Small starch granules contain 25% more ester-bound phosphate per glucose residue than large starch granules. l h e degree of phosphorylation was found to be almost constant during tuber development. lsolated tuber discs synthesize starch from externally supplied glucose at a significant rate. Tuber discs supplied with glucose and [3ZP]orthophosphate incorporate radiolabeled phosphorus into the starch. l h e level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 14 publications
0
62
0
Order By: Relevance
“…Likewise, in potato leaves, starch phosphorylation occurs also during biosynthesis, as indicated by the similar levels of starch-bound Glc6P in light and darkness (Table I). Thus, transitory starch is phosphorylated during synthesis, as it has previously been documented for reserve starch in potato amyloplasts (Nielsen et al, 1994;Wischmann et al, 1999). However, here we show that during breakdown of transitory starch, phosphorylation occurs at an even higher rate.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Likewise, in potato leaves, starch phosphorylation occurs also during biosynthesis, as indicated by the similar levels of starch-bound Glc6P in light and darkness (Table I). Thus, transitory starch is phosphorylated during synthesis, as it has previously been documented for reserve starch in potato amyloplasts (Nielsen et al, 1994;Wischmann et al, 1999). However, here we show that during breakdown of transitory starch, phosphorylation occurs at an even higher rate.…”
Section: Discussionmentioning
confidence: 38%
“…However, experimental evidence is lacking. Nielsen et al (1994) have shown that potato tuber starch is phosphorylated during biosynthesis. This result, in combination with the more recent findings (Lorberth et al, 1998;Yu et al, 2001;Ritte et al, 2002), suggests that phosphate incorporation during starch synthesis somehow determines the degradability of the starch particle.…”
mentioning
confidence: 99%
“…Under in vivo conditions, phosphorylation of native starch particles occurs both during net biosynthesis (Nielsen et al, 1994) and net degradation, but, at least in chloroplasts, the rate of phosphorylation is higher during net starch mobili-(a) (b) (c) Figure 5. MALDI MS analysis of purified phosphoglucans.…”
Section: Discussionmentioning
confidence: 99%
“…For enzymatic G-6-P quantification, the GWD assay mixtures were hydrolyzed in 0.7 N HCl (4 h at 95°C). Following neutralization with 0.7 N NaOH, G-6-P was quantified enzymatically (Nielsen et al, 1994). For TLC analyses, samples were hydrolyzed in 2 M TFA (2 h at 95°C), dried under vacuum, dissolved in water and dried again.…”
Section: Enzymatic Assays and Labeling Experimentsmentioning
confidence: 99%
“…The amylose content of the purified starch was measured by two different methods ; first by quantitatively precipitating the amylopectin using the lectin Concanavalin A according to the instructions from a kit (Megazyme International), and secondly by an iodine-binding assay [18]. The glucose 6-phosphate content of the starch was measured using the enzyme glucose 6-phosphate dehydrogenase after acid hydrolysis of the starch [19].…”
Section: Measurement Of Starch and Its Amylose And Phosphate Contentsmentioning
confidence: 99%